Mutations in the BAF-complex subunit DPF2 associated with Coffin-Siris syndrome - Vasileiou, G; Vergarajauregui, S; Endele, S; Popp, B; Büttner, C; Ekici, AB; Gerard, M; Bramswig, NC; Albrecht, B; Clayton-Smith, J; Morton, J; Tomkins, S; et al. (Cell Press, 2018)
Variants affecting the function of different subunits of the BAF chromatin remodelling complex lead to various neurodevelopmental syndromes including Coffin-Siris syndrome. Furthermore, variants in proteins containing PHD fingers, motifs recognizing specific histone tail modifications, have been associated with several neurological and developmental delay disorders. Here we report 8 heterozygous de novo variants, 1 frameshift, 2 splice site and 5 missense, in the gene encoding the BAF complex subunit double plant homeodomain finger 2 (DPF2). Affected individuals share common clinical features described in individuals with Coffin-Siris syndrome including coarse facial features, global developmental delay, intellectual disability, speech impairment and hypoplasia of finger and toenails. All variants occur within the highly conserved PHD1 and PHD2 motifs. Moreover, missense variants are situated close to zinc binding sites and are predicted to disrupt these sites. Recombinant protein and histone peptide pull-down assays revealed that a subset of the identified missense variants abolished or impaired DPF2 binding to unmodified and modified H3 histone tails. These results suggest an impairment of PHD fingers structural integrity and cohesion and likely an aberrant recognition of histone modifications. Furthermore, in HEK293 and COS7 cell lines the overexpression of these variants was associated with nuclear aggregate formation and recruitment of both wild-type DPF2 and BRG1 to these aggregates. Expression analysis of truncating variants found in individuals, indicated that the aberrant transcripts escape nonsense-mediated decay. Taken together, we provide compelling evidence that de novo variants in DPF2 cause Coffin-Siris syndrome and propose a dominant negative mechanism of pathogenicity.